(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, praised by His grace, worshiped by His power, obeyed by His authority, desired by what He has, feared of His punishment, enforceable by His command in His earth and heaven, who created the creation by His power, distinguished them by His rulings, honored them with His religion, and honored them with His Prophet Muhammad, may God’s prayers and peace be upon him and his family, then God Almighty And may God make intermarriage a later lineage, and a presumptive matter, and he strengthened the wombs with it, and committed them to the sleepers, and I pray and greet his good and pure household from whom God removed the uncleanness and purified them with a purification, and his companions, the righteous immigrants and supporters, and those who follow his right path until the Day of Judgment.